Development of RLC Teaching Aids as Learning Media for Alternating Voltage Circuits to Improve Student Learning Outcomes - Lhutfia Nurjannah; Imam Sucahyo (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
Learning media is a tool to facilitate the delivery of learning materials. Unfortunately, learning media, especially in Physics, was found to be lacking at the secondary school level. This study aims to develop appropriate teaching aids with valid, practical, and effective criteria for improving student physics learning outcomes. This research is an R&D (Research and Development) research with the ADDIE model (Analyze, Design, Develop, Implement, and Evaluation). The validity of the teaching aids is determined based on the validation results of three expert validators, and the student's response determines the practicality of the teaching aids after learning. The effectiveness of teaching aids is determined based on student learning outcomes in the aspect of knowledge. The study used a one-group pretest-posttest design with 29 grade XII students of SMA Tamansiswa Mojokerto as the subject. The results showed that the RLC series of teaching aids developed (1) were categorized as very valid, (2) students gave a positive response to the use of RLC teaching aids, and (3) student learning outcomes were stated to have increased in the moderate category. Based on the study results, it can be concluded that the RLC teaching aids that were developed are feasible (valid, practical, and effective) to be used as learning media to improve the learning outcomes of class XII students of SMA Tamansiswa Mojokerto.